Strategi Pengembangan Komoditas Kopi di Kecamatan Latimojong Kabupaten Luwu - Nur Afni Sawar; Ihsan Ihsan; Isfa Sastrawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2022)
Latimojong sub-district is one of the coffee-producing sub-districts in Luwu Regency and the sub-district of agricultural designation contained in the Luwu Regency Strategic Plan and Luwu Regency RTRW 2012-2032. This study aims to determine the characteristics, potentials and problems of coffee commodities in Latimojong District, and to formulate strategic ideas for developing coffee commodities in Latimojong District, Luwu Regency. Data was collected by using interview techniques, questionnaires, observations and literature studies. The analysis was carried out using descriptive qualitative and quantitative methods, spatial analysis, LQ analysis, DLQ analysis, demand analysis, comparative analysis or productivity analysis, Likert scale analysis, and SWOT analysis. This study shows the characteristic conditions of Latimojong District that support coffee commodity activities based on studies of physical conditions, namely altitude, rainfall, slope and land use as well as non-physical studies, namely the basic LQ value and prospective DLQ. This study also shows that Latimojong District has the potential for coffee commodities that can be developed in the form of extensive plantation land potential, adequate human resources based on quantity, surplus coffee production and constant demand for coffee and there are problems in the form of accessibility, facilities and marketing of coffee. The conclusion of this study is to recommend 7 strategic ideas, namely WO (Weaknesses-Opportunities). This strategy was made by minimizing the weaknesses of Latimojong District and take advantage of opportunities to develop coffee commodities.